Determinants that influence the informality of the vulnerable area of the Briceño-San Vicente Beach profile - Alcívar-Intriago, Andrés Aladino; Valencia- Castro, Fátima Acnabel; Zambrano-Gómez, María Gabriela; Moreira-Castro, Silvia Alexandra; Palacios-Dueñas, Ana Katerine (International research journal of management, IT and social sciences, 2024)
A correct vulnerability assessment will allow, in the long term, to make better decisions when making comprehensive coastal plans, planning the construction of sites for industry, ports, tourist housing. The objective was to analyze the determinants that influence the informality of the vulnerable area of the Briceño beach profile of the San Vicente canton, province of Manabí; in the period from March to June 2023. The bibliographic review and field, experimental and transectional research were used as methodology. The information was obtained through participatory observation and the survey was used as an instrument, designed by the proposed variables. The result was that, of the 30 families surveyed, segregation and informality are three-dimensional phenomena: Residentially: 53% of the families live in a precarious state, 30% in a regular state and 17% in a state of satisfactory housing; That is to say, they do not have architectural spatial organization, nor standardized setbacks between homes.